2021
DOI: 10.1371/journal.pone.0255435
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the purchase behaviour of farmers’ markets consumers

Abstract: The main purpose of this study is to determine the factors that motivate consumers who shop at farmers’ markets. The data for this study were gathered from questionnaires of 363 consumers from eight farmers’ markets in seven districts of Izmir province, Turkey. To reveal the consumer profile of the farmers’ markets examined in this study, consumer segments were determined using factor and cluster analysis. Two different consumer segments—‘conventional’ and ‘conscious’—were identified in the farmers’ markets ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…As for demographics in the Ecomercado, there seems to be some clear patterns. One of the most prevalent patterns observed is that farmers' markets seem to be more frequented by women than by men, which is aligned with other farmers' markets in similar countries, where several studies showed that the percentage of female consumers was significantly higher than the percentage of males [23,27,29,[33][34][35][36][37][38], only in the case of India it was completely the opposite, probably because of cultural reasons [24].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As for demographics in the Ecomercado, there seems to be some clear patterns. One of the most prevalent patterns observed is that farmers' markets seem to be more frequented by women than by men, which is aligned with other farmers' markets in similar countries, where several studies showed that the percentage of female consumers was significantly higher than the percentage of males [23,27,29,[33][34][35][36][37][38], only in the case of India it was completely the opposite, probably because of cultural reasons [24].…”
Section: Discussionmentioning
confidence: 66%
“…Considering all the benefits that short supply chains in general, and farmers' markets in particular, bring to the local community and the environment, it is a scientific necessity to study these short food supply chains and obtain information to promote them. However, despite finding numerous studies in the United States and Europe [22][23][24][25][26][27][28][29], there is a literature gap in the region of Andalusia, in southern Spain, especially in long-term studies. In addition, this is the first study that focuses on the Ecomercado of Granada.…”
Section: Introductionmentioning
confidence: 99%
“…(2017), the global agri‐food value chain is executed mainly through channels oriented to supermarkets. Regarding the Persian lime sale at packing facilities (image M5), this lime is considered important due to its freshness, which has an influence on the consumer's purchase decision (Adanacioglu, 2021). In the case of the results of the images M2 and M3, this could be due to the fact that the context shown in these images generates wide deviations from the expectations that these consumers have towards the product, which may be generating disgust or neophobia for the product (Pliner & Hobden, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…For example, housewives look for products as mothers and family caregivers influencing the formation of the family eating behaviours (Eljamay et al ., 2022; Nevedida et al ., 2022). In contrast, conventional consumers have a typical behaviour giving importance to factors such as the location of the market, the quality, and freshness of the products (Adanacioglu, 2021). However, producers as consumers have been scarcely studied in research involving sensory and cognitive aspects of their own produce (Ramírez‐Rivera et al ., 2018; Carfora et al ., 2019; Lee et al ., 2020) even when they influence the concerns of other consumers (Torjusen et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…FNPE have some similarities with initiatives such as farmers markets, mobile markets, farm stands, and cost-offset community-supported agriculture, which are part of public Food and Nutrition Security policies in many countries in Latin America [11], Europe [28][29][30][31][32] and also in the United States [33][34][35]. In Brazil, FNPE are structural elements of the National Food and Nutritional Security Policy [23,24].…”
Section: Introductionmentioning
confidence: 99%